A Shooting and Control Application of Four-Legged Robots with a Gun Turret - Tatar, Ahmet Burak; Tasar, Beyda; Yakut, Oguz (Springer Heidelberg, 2020)
This study aims at designing and modeling a four-legged (quadruped) mobile robot and a movable gun turret placed on this robot. Gun barrel stabilization was carried out with the PID control method in order to increase the success of the system in target tracking and ballistic control. The success of the designed stabilizer was tested by simulating shots for fixed targets while the four-legged robot walked at a constant speed. The system was tested for ten different scenarios, and the results were presented with tables and graphs. The mean tracking error value of scenarios was as 0.099 m, and the standard deviation was 0.0443. The results show that a four-legged robot with a movable gun turret can be used in practical applications in the defense industry with the proposed ballistic stabilization method.
Keywords: Four-legged robot; Gun barrel stabilization; PID control; Kinematic; Dynamic